Dynamic High-Cadence Cycling Improves Motor Symptoms in Parkinson’s Disease - Ridgel, Angela L.; Phillips, Robert S.; Walter, Benjamin L.; Discenzo, Fred M.; Loparo, Kenneth A. (Frontiers in Neurology, 2015)
Rationale: Individuals with Parkinson’s disease (PD) often have deficits in kinesthesia. There is a need for rehabilitation interventions that improve these kinesthetic deficits. Forced (tandem) cycling at a high cadence improves motor function. However, tandem cycling is difficult to implement in a rehabilitation setting. Objective: To construct an instrumented, motored cycle and to examine if high cadence dynamic cycling promotes improvements in motor function. Method: This motored cycle had two different modes: dynamic and static cycling. In dynamic mode, the motor maintained 75-85 rpm. In static mode, the rider determined the pedaling cadence. UPDRS Motor III and Timed Up and Go (TUG) were used to assess changes in motor function after three cycling sessions. Results: Individuals in the static group showed a lower cadence but a higher power, torque and heart rate than the dynamic group. UPDRS score showed a significant 13.9% improvement in the dynamic group and only a 0.9% improvement in the static group. There was also a 16.5% improvement in TUG time in the dynamic group but only an 8% improvement in the static group. Conclusion: These findings show that dynamic cycling can improve PD motor function and that activation of proprioceptors with a high cadence but variable pattern may be important for motor improvements in PD.